(untitled) (SCIENCE TIME JOURNAL, 2025)
This study examines the linguistic and pragmatic mechanisms underlying communication between detectives and suspects in detective fiction. Drawing on dialogues from Arthur Conan Doyle’s works and selected contemporary detective narratives, the research identifies dominant politeness strategies, institutional power markers, speech act patterns, and interrogation tactics shaping investigative discourse. The findings reveal that detectives typically employ direct directives, presupposition-based questioning, and coercive interrogatives to assert institutional authority, while suspects rely on indirectness, avoidance, mitigation, hesitation, and self-protective pragmatic strategies to manage face-threatening situations. The study demonstrates that politeness strategies in detective–suspect communication function not only as communicative tools but also as indicators of psychological tension, hierarchical imbalance, and narrative progression. These results contribute to a deeper understanding of the role of linguopragmatics in the structure of detective narratives.